Study of Composition and Composition of Macro Algae Habitat in the Intertidal Zone Water of Sibu Island, Nort Oba District Tidore Islands City Nort Maluku - Sukmawati Djalil; Riyadi Subur; Rina Rina; Sunarti Sunarti; Yuyun Abubakar; Aryati A. Fadel; Adi Noman Susanto; Sarni Sarni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Macro algae is a part of marine plants whose whole body is called the